Who is in Control? Clinicians' View on Their Role in Self-management Approaches: A Qualitative Metasynthesis - Mudge, S; Kayes, NM; McPherson, KM (BMJ Open, 2015)
Objective: To explore clinician perceptions of involvement in delivery of self-management approaches. Setting: All healthcare settings. Design: EBSCO, Scopus and AMED databases were searched, in July 2013, for peer-reviewed studies in English reporting original qualitative data concerning perceptions of clinicians regarding their involvement in or integration of a self-management approach. Of 1930 studies identified, 1889 did not meet the inclusion criteria. Full text of 41 studies were reviewed by two independent reviewers; 14 papers were included for metasynthesis. Findings and discussion sections were imported into Nvivo-10 and coded line-by-line. Codes were organised into descriptive themes and cross-checked against original sources to check interpretation, and refined iteratively until findings represented an agreed understanding. Studies were appraised for quality. Results: Delivering self-management in practice appeared to be a complex process for many clinicians. The issue of ‘control’ arose in all studies, both in the qualitative data and authors’ interpretations. The first theme: Who is in control?—represented ways clinicians talked of exercising control over patients and the control they expected patients to have over their condition. The second theme: Changing clinician views—reflected what appeared to be an essential transformation of practice experienced by some clinicians in the process of integrating self-management approaches into the practice. A range of challenges associated with shifting towards a self-management approach were reflected in the third theme, Overcoming challenges to change. Tensions appeared to exist around forming partnerships with patients. Strategies found helpful in the process of change included: dedicating time to practice reciprocity in communication style, peer support and self-reflection. Conclusions: A consistent finding across studies is that ‘control’ is a key feature of how self-management is viewed by clinicians. They described challenges associated with the paradigm shift required to share or let go of control. Future research should identify whether strategies described by clinicians are key to successful self-management.
Keywords: Health occupations; Professional practice; Self-management